A Not-So-Simple Graph (Part II)

If you have not checked out Part I of the problem, click here . Part I is less challenging, and my solution to that problem might give you inspiration for solving Part II.

Consider a graph with vertices t 1 , t 2 , t 3 , . . . , t k t_{1},t_{2},t_{3},...,t_{k} , where k Z + , k 2 k \in \mathbb{Z}^{+},k≥2 . For every integer pair ( m , n ) (m,n) where k m > n 1 k≥m>n≥1 , there are ( m n ) (m-n) distinct edges connecting t m t_{m} to t n t_{n} . No edges intersect. An ant moves along the edges of the graph. Given that it can only move from t a t_{a} to t b t_{b} if a > b a>b , the number of distinct ways it can move from t k t_{k} to t 1 t_{1} can be expressed as A ( B ) k C ( D ) k A(B)^{k}-C(D)^{k} , where A , B , C , D A,B,C,D are positive numbers. Find 10 A C + B + D 10AC+B+D .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sam Zhou
May 31, 2019

Let x k x_{k} denote the number of ways the ant can move from t k t_{k} to t 1 t_{1} . By inspection, x 2 = 1 x_{2}=1 and x 3 = 3 x_{3}=3 .

We can define x k x_{k} recursively, and can deduce that x k = i = 1 k 1 ( k i ) x i = x k 1 + i = 1 k 2 ( k i ) x i = x k 1 + i = 1 k 2 ( k 1 i ) x i + i = 1 k 2 x i = 2 x k 1 + i = 1 k 2 x i x_{k}=\sum_{i=1}^{k-1} (k-i)x_{i}=x_{k-1}+\sum_{i=1}^{k-2} (k-i)x_{i}=x_{k-1}+\sum_{i=1}^{k-2} (k-1-i)x_{i}+\sum_{i=1}^{k-2} x_{i}=2x_{k-1}+\sum_{i=1}^{k-2} x_{i} .

Notice that i = 1 k 2 x i = x k 1 x k 2 \sum_{i=1}^{k-2} x_{i}=x_{k-1}-x_{k-2} . Therefore, x k = 3 x k 1 x k 2 x_{k}=3x_{k-1}-x_{k-2} . We can now solve this recurrence relation.

The auxiliary equation λ 2 3 λ + 1 = 0 \lambda^{2}-3\lambda+1=0 and has roots 1 2 ( 3 + 5 ) \frac{1}{2} (3+\sqrt{5}) and 1 2 ( 3 5 ) \frac{1}{2} (3-\sqrt{5}) . These two values are B B and D D respectively.

Plug the two values and the initial conditions ( x 2 = 1 x_{2}=1 and x 3 = 3 x_{3}=3 ) into the equation x k = A ( B ) k C ( D ) k x_{k}=A(B)^{k}-C(D)^{k} to get A = 1 10 ( 3 5 5 ) A=\frac{1}{10} (3\sqrt{5}-5) and C = 1 10 ( 3 5 + 5 ) C=\frac{1}{10} (3\sqrt{5}+5) .

As 10 A C = 2 10AC=2 and B + D = 3 B+D=3 , the answer is 5 \boxed{5} .

Nice solution! It is also interesting to note that the terms of x k x_k are every other number in the Fibonacci sequence!

David Vreken - 2 years ago

Great solution Sam! I agree with David Vreken who mentioned above that the xk's are numbers in the Fibonacci sequence. I noticed this and used the general formula for Fibonacci sequence terms to find the solution to this problem. By the way, this is a great problem that you should consider sending to MAA so it may be incorporated into the AIME exam!

Bochuan Zhang - 2 years ago

Thanks! I only realized this interesting pattern after I figured out the solution to this problem :)

Sam Zhou - 2 years ago
K T
Jun 3, 2019

Suppose the number of ways to traverse a distance k = m n k=m-n is f(k).

Since we can do the first step of size j to any lower in vertex in j ways, we have the recursion relationship: f ( k ) = j = 1 k j f ( k j ) f(k) = \sum_{j=1}^k{j f(k-j)} , with f ( 0 ) = 1 f(0)=1 , or

f ( k ) = 1 × f ( k 1 ) + 2 × f ( k 2 ) + . . . + k × f ( 0 ) f(k) =1×f(k-1)+2×f(k-2)+... +k×f(0) . This way we find f ( 1 ) = 1 , f ( 2 ) = 1 , f ( 3 ) = 3 , f ( 4 ) = 8 , f ( 5 ) = 21 , f ( 5 ) = 55 , . . . f(1)=1, f(2)=1, f(3)=3, f(4)=8, f(5)=21,f(5)=55, ... . These are the even indexed Fibonacci numbers F n F_n where n = 2 k 2 n=2k-2 . Using Binets formula: f ( k ) = F 2 k 2 = φ 2 k 2 ψ 2 k 2 5 = ( φ 2 ) k φ 2 5 ( ψ 2 ) k ψ 2 5 f(k) = F_{2k-2} =\frac{φ^{2k-2}-ψ^{2k-2}}{\sqrt{5}}=\frac{(φ^2)^{k} }{φ^2 \sqrt{5}} - \frac{(ψ^2)^{k}}{ ψ^2\sqrt{5}}

So A = 1 φ 2 5 = 0.170820... A= \frac{1}{φ^2 \sqrt{5}} = 0.170820... B = φ 2 = 2.618033... B= φ^2 = 2.618033... C = 1 ψ 2 5 = 1.170820... C= \frac{1}{ψ^2 \sqrt{5}} =1.170820... D = ψ 2 = 0.381966... D= ψ^2=0.381966...

And 10 A C + B + D = 2 + 3 = 5 10AC+B+D=2+3 =\boxed{5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...